Nucleic acid-binding molecules with high affinity and base sequence specificity: intercalating agents covalently linked to oligodeoxynucleotides. - Asseline, U (1984)
Oligodeoxyribonucleotides covalently linked to an intercalating agent via a polymethylene linker were synthesized. Oligothymidylates attached to an acridine dye (Acr) through the 3'-phosphate group [(Tp)n(CH2) mAcr ] specifically interact with the complementary sequence. The interaction is strongly stabilized by the intercalating agent. By using absorption and fluorescence spectroscopies, it is shown that complex formation between (Tp)n(CH2) mAcr and poly(rA) involves the formation of n A X T base pairs, where n is the number of thymines in the oligonucleotide. The acridine ring intercalates between A X T base pairs. Fluorescence excitation spectra reveal the existence of two environments for the acridine ring, whose relative contributions depend on the linker length (m). The binding of (Tp)4(CH2) mAcr to poly(rA) is analyzed in terms of site binding and cooperative interactions between oligonucleotides along the polynucleotide lattice. Thermodynamic parameters show that the covalent attachment of the acridine ring strongly stabilizes the binding of the oligonucleotide to its complementary sequence. The stabilization depends on the linker length; the compound with m = 5 gives a more stable complex than that with m = 3. These results open the way to the synthesis of a family of molecules exhibiting both high-affinity and high-specificity for a nucleic acid base sequence.